Corps enquêteurs et lieux performés - Valérie Lebois; Dominique Laburte (Ambiances)
Teaching the sensory experience of architecture is a necessity as the means of design features become increasingly immaterial. For this reason, a method based on a principle of active pedagogy is proposed, where the student learns by acting, based on interactions between the body and the atmosphere of a place. A first step is to investigate the atmosphere through physical exercises, designed to retain the attention of students. A second stage asks them to provide the results of the investigation through the design and the realization of an embodied performance. This article summarizes the work of students in first and second year of Master’s degree at the Graduate School of Architecture of Strasbourg, immersed in the spaces of the Malraux multimedia library in Strasbourg.